STUDENTS’ BACKGROUND TOWARDS LEARNING ENGLISH OUT OF CLASSROOM SETTING - Luthfiyatun Thoyyibah (Universitas Galuh, 2019)
There have been many facts showed that senior high school students in Indonesia faced some problems in learning English at school. Because of that, students try to seek a solution which offered outside the class, commonly known as independent language learning. Because there are limited studies elaborated activity of learning English out of school context, thus this paper aims to explore what kind of activity that the senior high school students choose for learning English out of the school context. This study employed qualitative descriptive study. Data were drawn from questionnaires that were disseminated to 40 students of state and private senior high schools, in order to respond with their own views. Based on the findings of this study, activity of learning English that mostly conducted by students from state school is attending extra course while most of students from private school prefer individual learning. According to the findings, this study recommends the further study of the similar field involving a bigger number of respondents and enrichment of the theory. Keywords: state school, private school, independent learning, extra course